y = 3x + 6 y = -13x - 4

1 answer

The given equations are:

y = 3x + 6 (equation 1)
y = -13x - 4 (equation 2)

We can solve this system of equations by equating the right side of both equations:

3x + 6 = -13x - 4

Now, let's solve for x:

3x + 13x = -4 - 6

16x = -10

Dividing both sides by 16:

x = -10/16
x = -5/8

Now, substitute the value of x back into one of the equations to find the value of y.
Using equation 1,

y = 3(-5/8) + 6
y = -15/8 + 48/8
y = 33/8

Therefore, the solution to the system of equations is x = -5/8 and y = 33/8.